The Big bang theory and philosophy : rock, paper, scissors, Aristotle, Locke (The Blackwell philosophy and pop culture series, 2012)
"There are books that debate math, science, and history; there are books that help you build walls or even pyramids; there are even books that discuss Neanderthals with tools and autotrophs that drool. This book discusses philosophy. But you don't need an IQ of 187 to enjoy it. I swear to cow! As you'll see, the philosophy is theoretical, but the fun is real"--